Experimental And Computational Studies Of The Hydrodynamics Of The Riser Of A Circulating Fluidized Bed - Hussain, A.; Ani, F.N.; Darus, A.N.; Mustafa, A. (2005)

(untitled)
The hydrodynamics of a circulating fluidized bed (CFB) risers is highly complex and is strongly influenced by the distribution of particles, which is governed by the amount of particles, size, form (e.g. spherical or elliptic), density, etc. The CFB riser column has 265 rnrn (width), 72 mrn (depth) cross-section (rectangle) and 2.7 m height. The riser is made up of interchangeable Plexiglas columns. In this study the influence of the amount of particles on the flow pattern in the CFB system is investigated. The particle loading is increased from a dilute to a dense and gas-particle flow is analyzed. Simulations were done using FLUENT 6.1, a CFD package by Fluent Inc. Palm shell particles and air were used as the solid and gas phases, respectively. The 2D simulations were done using the geometrical configuration of a CFB test rig at the Universiti Teknologi Malaysia (UTM). The result discusses the variation of velocity contours, along the riser column and in the riser exit geometry. The effect is significant in the upper region of the riser column and the velocity contours are also influenced by the exit geometry. Simulations results predict that the riser exit cause an upstream exit region of increased solid volume fraction. Experimental and computational results are matched to reasonable agreement. Experimental findings have also helped to refine the numerical modelling of multiphase CFB system.